Wnt11 directs nephron progenitor polarity and motile behavior ultimately determining nephron endowment - O'Brien, Lori L; Combes, Alexander N; Short, Kieran M; Lindström, Nils O; Whitney, Peter H; Cullen-McEwen, Luise A; Ju, Adler; Abdelhalim, Ahmed; Michos, Odyssé; Bertram, John F; Smyth, Ian M; Little, Melissa H; et al. (eLife, 2018)
A normal endowment of nephrons in the mammalian kidney requires a balance of nephron progenitor self-renewal and differentiation throughout development. Here, we provide evidence for a novel action of ureteric branch tip-derived Wnt11 in progenitor cell organization and interactions within the nephrogenic niche, ultimately determining nephron endowment. In Wnt11 mutants, nephron progenitors dispersed from their restricted niche, intermixing with interstitial progenitors. Nephron progenitor differentiation was accelerated, kidneys were significantly smaller, and the nephron progenitor pool was prematurely exhausted, halving the final nephron count. Interestingly, RNA-seq revealed no significant differences in gene expression. Live imaging of nephron progenitors showed that in the absence of Wnt11 they lose stable attachments to the ureteric branch tips, continuously detaching and reattaching. Further, the polarized distribution of several markers within nephron progenitors is disrupted. Together these data highlight the importance of Wnt11 signaling in directing nephron progenitor behavior which determines a normal nephrogenic program.